Ovarian masses with papillary projections diagnosed and removed during pregnancy: ultrasound features and histological diagnosis. (July 2017) - Mascilini, F.; Savelli, L.; Scifo, M. C.; Exacoustos, C.; Timor‐Tritsch, I. E.; De Blasis, I.; Moruzzi, M. C.; Pasciuto, T.; Scambia, G.; Valentin, L.; Testa, A. C.
ABSTRACT: Objective: To elucidate the ultrasound features that can discriminate between benign and malignant ovarian cysts with papillary projections but no other solid component in pregnant women. Methods: Thirty‐four women with an ultrasound diagnosis of an ovarian cyst with papillary projections but no other solid component that had been removed surgically during pregnancy were identified from the databases of four ultrasound units. Some clinical and ultrasound information was collected prospectively. Missing information was obtained retrospectively from ultrasound images, ultrasound reports and patient records. Using prospectively and retrospectively collected data, the ultrasound appearance of the tumors was described using the terms and definitions of the International Ovarian Tumor Analysis group. The ultrasound characteristics were compared with the histological diagnosis. Results: Of the 34 cases included, 19 (56%) lesions were benign (16 decidualized endometriomas, one cystadenofibroma, one simple cyst, one struma ovarii), 12 (35%) were borderline tumors and three (9%) were primary invasive tumors (two immature teratomas, one endometrioid cystadenocarcinoma). The contour of the cyst papillations was smooth in 79% (15/19) of benign tumors vs 27% (4/15) of malignant tumors ( P  = 0.002). The cystic content showed ground‐glass echogenicity in 74% (14/19) of benign tumors vs 13% (2/15) of malignant tumors ( P  = 0.0006). All ovarian masses with smooth papillations and ground‐glass content ( n  = 12) were decidualized endometriomas. The papillary projections were vascularized and the color score was 3 or 4 in 88% (14/16) of decidualized endometriomas vs 42% (5/12) of borderline tumors ( P  = 0.013). Conclusions: In pregnant women, ovarian cysts with ground‐glass echogenicity and papillations with a smooth contour on ultrasound are most likely to be decidualized endometriomas. Cysts with anechoic or low‐level echogenicity and papillations with an irregular contour suggest borderline malignancy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.